George Bush : a president's story - Westfeldt, Wallace; Wilson, David S.; Florescu, John M.; Frost, David ([Estados Unidos] : A&E Network, 1998)
Resumen
Music composed by David Arnold
David Frost
Diálogo en inglés
Keywords: PRESIDENTES; ESTADOS UNIDOS DE AMERICA; Bush,George Herbert Walker, -- 1924-; BIOGRAFIAS; VIDEOGRABACIONES